Squat task as an assessment tool for detecting injury risk: A systematic review. - Avcı, Ender Ersin; Kartal, Gökçe; Çakır, Furkan; Polat, Mine Gülden; Demirbüken, İlkşan (Journal of Bodywork & Movement Therapies, 2026)
The squat is a fundamental movement that is frequently performed in both daily life activities and sports. The aim of this systematic review was to identify and systematize evidence from the literature that relates the isolated squat movement to musculoskeletal injury risk assessment. A comprehensive literature search was conducted using Web of Science, PubMed, Scopus and ScienceDirect databases and Boolean operators. The study was registered in PROSPERO. Risk of bias assessment was performed using the National Heart, Lung, and Blood Institute (NHLBI) Observational Cohort and Cross-Sectional Studies assessment tools. The quality of the studies was assessed in accordance with the previously established research criteria. A total of 7 studies were included out of the 4966 studies collected. The included studies were published between 2015 and 2023. The included studies demonstrated that different squat types such as double leg squat, single leg squat and overhead squat were used in injury risk assessment. Despite methodological differences between the included studies, the results showed that squatting can be used for injury risk assessment. Two studies have concluded that squat alone is not sufficient to assess the risk of injury. The squat task can provide convenience to clinicians when assessing the risk of injury, with its advantages such as ease of application and no equipment required. PROSPERO (ID: CRD42023479944).